2012
DOI: 10.4025/actascihealthsci.v34ispec.10264
|View full text |Cite
|
Sign up to set email alerts
|

The influence of household environment on caregivers’ overload of children with cerebral paralysis

Abstract: ABSTRACT. The environment is considered an extremely important factor in individuals' health promotion and life quality. The influence that the environment exerts on caregivers' lives is due to all the complications they have to experience. Current study investigates the influence of family environment on the overload of caregivers of children with cerebral paralysis. The research comprised 21 caregivers, whose overload intensity was assessed by three instruments: a caretaker characterization form, Zarit Careg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“… 25 27 Overall health and social environment factors included quality of life, 16 25 social support 25 and environment. 18 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 25 27 Overall health and social environment factors included quality of life, 16 25 social support 25 and environment. 18 …”
Section: Resultsmentioning
confidence: 99%
“…25 27 Overall health and social environment factors included quality of life, 16 25 social support 25 and environment. 18 Quality of evidence for potential factors Quality of evidence for potential factors of caregiver burden are presented in online supplemental table. The criteria for compelling evidence are that each factor was measured in at least three studies that reported significant relationships.…”
Section: Caregiver Factorsmentioning
confidence: 99%